Competencies of Alpine Skiing Coaches - Gašperin, Timi; Podbregar, Iztok; Vasić, Bojana; Dežman, Marina (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Competencies are the set of knowledge, skills, experiences and attitudes needed to function effectively in everyday life, whether at work or at home. Competencies play an important role in the world of work, and this is no different in Alpine skiing. In alpine skiing, coaches and team leaders need specific competencies to be able to lead athletes successfully. Putting these competencies into practice is crucial for the development of athletes and the achievement of top results. Technical skills are key, but the ability to lead, motivate and strategically plan the training and competitions themselves should not be neglected. The aim of this paper is to identify the core competencies of alpine ski coaches needed to successfully perform coaching tasks. It was found that it is important for coaches to possess both technical and soft competencies for their success, among which motivation and adapting training to individuals stand out.